2008
DOI: 10.1021/ma8005334
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Oxidation of High Performance Epoxy Networks: Correlation between the Molecular Mechanisms of Degradation and the Viscoelastic and Mechanical Response

Abstract: The photo-oxidative degradation of a highly cross-linked epoxide/diamine network has been investigated by FTIR spectroscopy, dynamic-mechanical thermal analysis (DMTA) and compressive mechanical tests. The FTIR measurements allowed us to monitor the degradation process and to obtain reliable kinetic data. Two dimensional infrared (2D IR) correlation spectroscopy, was employed to analyze the spectra collected as a function of time. This approach effectively enhanced the spectral resolution and revealed details … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…[6] It was found that for all profiles the best fit was achieved with a first order model (n ¼ 1), which yielded a very satisfactory description of the experimental data. The curves obtained by Equations 3 or 4 through a non-linear least-square regression of the experimental data are reported, as continuous lines, in Figures 2-4 that the methylene groups are the more susceptible to photo-oxidation and, possibly, the site of initiation of the whole process.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…[6] It was found that for all profiles the best fit was achieved with a first order model (n ¼ 1), which yielded a very satisfactory description of the experimental data. The curves obtained by Equations 3 or 4 through a non-linear least-square regression of the experimental data are reported, as continuous lines, in Figures 2-4 that the methylene groups are the more susceptible to photo-oxidation and, possibly, the site of initiation of the whole process.…”
mentioning
confidence: 80%
“…The first step of the curing schedule was carried out at 140 8C for 16 h, followed by a post-curing step at 200 8C for 4 h. Further details about the sample preparation are reported elsewhere. [6] The photoaging experiments were carried out at 50 8C and 50% of relative humidity in an environmental chamber equipped with a UV bulb lamp mainly emitting in the spectral range of 320-600 nm (simulating the solar spectrum). Transmission FTIR spectra were obtained using a PerkinElmer System 2000 spectrometer.…”
Section: Experimental Partmentioning
confidence: 99%
See 3 more Smart Citations